FACTORS AFFECTING MILLENIALS TO DONATE ONLINE AT KITABISA.COM - Wenti Krisnawati (Universitas muhammadiyah malang, 2021)
Background The donation-based crowdfunding model, which is used for fundraising, has proven to be successful in collecting aid funds, especially during natural disasters and other emergencies. The crowdfunding process occurs where a group of people (a large number) financially provide a relatively small amount of money as a donation or participate in support to fund a project that can potentially get a reward (Wicks, 2013: 5) The purpose of this research is to determine the effectiveness of the campaign, brand image and Innovation Platform on kitabisa.com. Design/methodology/approach research is focused on a quantitative approach. The population in this research were all students of the University of Muhammadiyah Gresik, a sample of 100 people, namely the Faculty of Economics and the Faculty of Teacher Training and Education. Data collection techniques from this research used a questionnaire. The analysis technique uses multiple linear regression with SPSS tools. Results and Discussion The results show that the effectiveness of the campaign is not significant, the hypothesis is rejected, with the development of advertising media in the current digital era unable to influence millennials to donate on the Kitabisa.com platform, while Brand Image, Platform Innovation have a positive effect and Platform innovation has a positive effect and significant to the Donation Decision. Research implications of Campaign Effectiveness, Brand image, Platform Innovation, provide great benefits to the Kitabisa.com platform in attracting donors to decide to donate on the Kitabisa.com platform.